(untitled) (Research, Society and Development, 2023)
The objective of this systematic review was to synthesize studies that evaluated the characteristics of 24-hour movement behavior in non-institutionalized elderly. This is research conducted in three electronic databases (PubMed, Web of Science and Scopus) from January to March 2022. Of the 395 studies found, 26 were included in the final analysis. The included studies showed good methodological quality (with a score of ≥ to 70%) and were conducted in 17 different countries. These studies were used objective (accelerometers) and/or subjective (questionnaires) measures to measure 24-hour movement behavior. The findings point to a low level of physical activity (PA), sedentary behavior (SB) and alteration and/or low sleep quality among the elderly. It was also observed, among the elderly, a greater concentration in the time dedicated to SB, when compared to the time dedicated to regular physical activity, and to sleep. However, there is a need for further studies in this area, especially longitudinal and experimental studies, with objective and subjective measures to help better understand 24-hour movement behaviors, and their possible implications for the health of the elderly.